2023
DOI: 10.3390/ijms24065712
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Neural Stem Cell Activation after Low-Intensity Focused Ultrasound-Induced Blood–Brain Barrier Modulation

Abstract: Endogenous neural stem cells (eNSCs) in the adult brain, which have the potential to self-renew and differentiate into functional, tissue-appropriate cell types, have raised new expectations for neurological disease therapy. Low-intensity focused ultrasound (LIFUS)-induced blood–brain barrier modulation has been reported to promote neurogenesis. Although these studies have reported improved behavioral performance and enhanced expression of brain biomarkers after LIFUS, indicating increased neurogenesis, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…And recently sonodynamic therapy, a combination of LIUS with a chemotherapeutic agent (sonosensitizer) has been explored as a promising alternative to cancer therapies [ 28 ]. In the field of stem cell research, LIPU promotes the expansion, differentiation, and migration of mesenchymal stem cells [ 29 , 30 ], and it has been reported that LIFU-induced BBB regulation can promote neurogenesis through the activation of endogenous neural stem cells [ 31 ]. In addition, LIPU can produce different biological effects on organs, tissues, and cells, and can be applied in fracture healing, cartilage repair [ 32 ], periodontal tissue regeneration [ 33 ], and alveolar bone regeneration [ 34 ].…”
Section: Clinical Application Of Fus In the Treatment Of Pdmentioning
confidence: 99%
“…And recently sonodynamic therapy, a combination of LIUS with a chemotherapeutic agent (sonosensitizer) has been explored as a promising alternative to cancer therapies [ 28 ]. In the field of stem cell research, LIPU promotes the expansion, differentiation, and migration of mesenchymal stem cells [ 29 , 30 ], and it has been reported that LIFU-induced BBB regulation can promote neurogenesis through the activation of endogenous neural stem cells [ 31 ]. In addition, LIPU can produce different biological effects on organs, tissues, and cells, and can be applied in fracture healing, cartilage repair [ 32 ], periodontal tissue regeneration [ 33 ], and alveolar bone regeneration [ 34 ].…”
Section: Clinical Application Of Fus In the Treatment Of Pdmentioning
confidence: 99%